Visible-light photoredox-catalyzed umpolung carboxylation of carbonyl compounds with CO2 - Guang-Mei Cao (Nature Portfolio, 2021)
Compounds bearing a carbonyl group, such as aldehydes and ketones, are important industrial chemicals and widespread in pharmaceuticals and natural products. Here, the authors report a strategy for visible-light photoredox-catalyzed umpolung carboxylation of diverse carbonyl compounds with CO2, to generate valuable α-hydroxycarboxylic acids.